Evaluation of Nutrient Composition of Moringa Leaf Meal from Different Location in East Nusa Tenggara, Indonesia - Maria A. Rane; Marsianus Perunggu; Catootjie L. Nalle (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The objective of the present study was to evaluate the nutrient composition of Moringa oleifera leaf meal (MLM) from different location in East Nusa Tenggara Province (ENT). A total of 27 samples of MLM were obtained from Sikka, Timor Tengah Utara and Kupang Regency. The experiment was designed using a block randomized design with three treatments and three replications (three samples per replication). The results showed that location significantly (P<0.05 â€“ 0.001) affected the dry matter (DM), crude lipid (CL)), crude fiber (CF), ash, phosphor (P), neutral detergent fiber (NDF), threonine, isoleucine,, leucine, serine, glutamic acid, glycine, alanine and proline contents of MLM. The DM, ash and CF of MLM from Kupang were lower (P<0.05) than those from two other locations. The location did not affect (P>0.05) the crude protein, gross energy, calcium and some amino acid contents of MLM.Â  The NDF of MLM from Sikka was lower (P<0.05) than those from Kupang and TTU. The concentration of P of MLM from Kupang and Sikka was higher (P<0.05) than that of TTU. In conclusion, the nutrients compositions of MLM were different according to the location where the plant grows. The MLM is rich in protein, Ca, good in amino acid profile and low in fiber content. Thus, the MLM is potential to be used as alternative protein source for poultry.